2008
DOI: 10.18268/bsgm2008v60n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Meyeria magna M’Coy, 1849 in Colombia: a widely distributed species during Aptian times

Abstract: Occurrence of the mecochirid decapod Meyeria magna M'Coy 1849 is documented based on numerous articulated specimens collected from upper Aptian strata of Colombia. This report represents the fi rst record in America for the species, previously reported from Aptian deposits of Europe. The numerous specimens of a relatively uniform size found in a single stratigraphic level suggests a mass mortality event, favorable conditions for the development of the community, or both. The stratigraphic range for the genus M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Etayo-Serna et al, 1969, 224). However, Durham (1946), Julivert (1968, 69) and Vega et al (2008) indicated that they have an Aptian range.…”
Section: Other Reported Barremian Depositsmentioning
confidence: 99%
“…Etayo-Serna et al, 1969, 224). However, Durham (1946), Julivert (1968, 69) and Vega et al (2008) indicated that they have an Aptian range.…”
Section: Other Reported Barremian Depositsmentioning
confidence: 99%
“…Glypheidean lobsters (Decapoda, Glypheidea) belong to a particularly specialized group of decapod crustaceans, which are highly diversified in the fossil record (Charbonnier et al, 2015), despite their low preservation potential when compared to other marine invertebrates (Kidwell and Flessa, 1995). In particular, the Mecochiridae family ( Van Straelen, 1925) has been the subject of many studies in recent times (Neto de Carvalho et al, 2003;Amati et al, 2004;Neto de Carvalho et al, 2007;Feldmann et al, 2007;Vega et al, 2008;Garassino et al, 2009;López-Horgue, 2009;De Grave et al, 2009;Schweitzer et al, 2010;Astrop, 2011;González-León et al, 2014Charbonnier et al, 2015;Breton et al, 2015;González-León et al, 2016;Neto de Carvalho, 2016 andRobin et al, 2016). Mecochiridae is considered to have 48 species within 7 genera (Schweitzer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%